A parallel FDTD algorithm using the MPI library. - Guiffaut, C.; Mahdjoubi, K.
In this paper, we describe the essential elements of a parallel algorithm for the FDTD method using the MPI (message passing interface) library. To simplify and accelerate the algorithm, an MPI Cartesian 2D topology is used. The inter-process communications are optimized by the use of derived data types. A general approach is also explained for parallelizing the auxiliary tools, such as far-field computation, thin-wire treatment, etc. For PMLs, we have used a new method that makes it unnecessary to split the field components. This considerably simplifies the computer programming, and is compatible with the parallel algorithm.
Keywords: Parallel algorithms; MPI; FDTA methods; Inter-process communication; Process topology; Multiprocessor interconnection; Perfectly matched layers